ULTRAVIOLET SPECTRUM OF EXTRACT OF CENTELLA ASIATICA (VALLARAI) IN EDIBLE OIL AS SUPPLEMENT - Pandian G, Soundra (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: The objective is to create 4 extracts of Centella Asiatica whole plants without using toxic chemicals based on an edible oil and water and to study the UV-vis absorption spectrum of the extracts. Methods: An extract of the whole plant was taken in fresh form with green leaves, made in to a paste by using an electric grinder and the paste mixed with water was heated with coconut oil at temperatures below 100 degree C. The oil part and water part of the extracts were then taken and analysed in an UV-vis spectrometer. The experiment was repeated by using Centella Asiatica whole plants dried in sun for a day. Results: The UV spectrum of the oil extract of undried Centella Asiatica whole plant showed absorption peaks at 413nm, 434 nm, 506nm, 537nm, 564nm, 610nm and 670nm. The oil extract of dried Centella Asiatica whole plant showed peaks at 413nm, and 670nm. The peaks between 434 nm and 670 nm in the oil extract were due to Chlorophyll. The strongest peak at 413 nm is the major signal of the extract and is thought to represent the flavonoid Rutin. The water part of the extract of the dried plants does not show any significant peak at 670nm of the chlorophyll. Conclusion: Four extracts of Centella Asiatica whole plant were studied. The oil part of the extracts showed a strong peak at 413 nm. The medicinal values of the 4 extracts of the plant need to be studied in detail.